The Protective Effect of Cortexin on Cisplatin-Induced Ototoxicity - Eroglu, Orkun; Karlidag, Turgut; Kuloglu, Tuncay; Keles, Erol; Kaygusuz, Irfan; Yalcin, Sinasi (Aves, 2018)
OBJECTIVE: The aim of this report is to evaluate whether cortexin provides any protective activity against ototoxicity of cisplatin. MATERIALS and METHODS: The study was performed on 30 healthy adult Wistar Albino rats, and rats were randomly divided into three groups of ten. Group I (Control group) was given intraperitoneal (ip) saline solution 1 mL/day. Group II (Cisplatin group) was given ip cisplatin for 2 days at doses of 10 mg/kg. Group III (Cisplatin + Cortexin group) was given ip cisplatin for 2 days at same doses with ip cortexin 2 mg/day for 7 days. Before and on the fourth day of the study, all subjects underwent auditory brainstem response (ABR) and distortion product otoacoustic emissions (DPOAE) tests. At the end of fourth day, half of the subjects in all three groups were decapitated, and their cochlea were removed for histopathologic examination. On the eighth day, tests of the remaining subjects and histopathological examinations were repeated. RESULTS: ABR tests on the fourth and eighth days showed elevations in the mean hearing thresholds of Groups II and III compared to Group I (p<0.05). DPOAE tests revealed a loss in emission values on the fourth and eighth days of the study compared to the baseline in Groups II and III. Comparison of Groups II with III showed that emission loss was higher in Group II at both time points, and the difference was more pronounced on the eighth day. Histopathological findings supported these tests. CONCLUSION: Cortexin provide protective activity against cisplatin-induced ototoxicity.
38th National Congress of Turkish Otorhinolaryngology and Head and Neck Surgery -- OCT 26-30, 2016 -- Antalya, TURKEY
Keywords: Cisplatin; cortexin; ototoxicity